Antibiotic treatment reduces the intensity of intraamniotic inflammation in pregnancies with idiopathic vaginal bleeding in the second trimester of pregnancy - Musilova, Ivana; Stranik, Jaroslav; Jacobsson, Bo; Kacerovsky, Marian (American journal of obstetrics and gynecology, 2024)
BACKGROUND: Idiopathic bleeding in the second trimester of pregnancy complicates <1% of all pregnancies. This pregnancy complication can be caused by alterations in local hemostasis in the decidua due to infection/inflammation in the choriodecidual niche. This condition is associated with intraamniotic inflammatory complications. Antibiotic therapy effectively reduces the intensity of intraamniotic inflammation in certain pregnancy pathologies. However, whether antibiotic administration can reduce the intensity of the intraamniotic inflammatory response or eradicate microorganisms in patients with idiopathic bleeding during the second trimester of pregnancy remains unclear. OBJECTIVE: This study primarily aimed to determine whether antimicrobial agents can reduce the magnitude of intraamniotic inflammation in patients with idiopathic bleeding in the second trimester of pregnancy by assessing the concentration of interleukin-6 in the amniotic fluid before and after 7 days of antibiotic treatment. The secondary aim was to determine whether treatment with a combination of antibiotics altered the microbial load of Ureaplasma species DNA in amniotic fluid. STUDY DESIGN: This retrospective cohort study included singleton-gestation patients with idiopathic bleeding between 15+0 and 27+6 weeks who underwent transabdominal amniocentesis at the time of admission. Follow-up amniocentesis was performed in a subset of patients unless abortion or delivery occurred earlier. Concentrations of interleukin-6 were measured in the amniotic fluid samples, and the presence of microbial invasion of the amniotic cavity was assessed using culture and molecular microbiological methods. Intraamniotic inflammation was defined as an interleukin-6 concentration ≥3000 pg/mL in the amniotic fluid samples. RESULTS: A total of 36 patients with idiopathic bleeding in the second trimester of pregnancy were included. All the patients underwent initial amniocentesis. Patients with intraamniotic inflammation (n=25) were treated using a combination of antibiotics consisting of intravenous ceftriaxone, intravenous metronidazole, and peroral clarithromycin. The patients without intraamniotic inflammation (n=11) were treated expectantly. In total, 25 patients delivered 7 days after admission. All patients with intraamniotic inflammation at the initial amniocentesis who delivered after 7 days underwent follow-up amniocentesis. Treatment with antibiotics decreased the interleukin-6 concentration in the amniotic fluid at follow-up amniocentesis compared with that at the initial amniocentesis in patients with intraamniotic inflammation (median [interquartile range]: 3457 pg/mL [2493-13,203] vs 19,812 pg/mL [11,973-34,518]; P=.0001). Amniotic fluid samples with Ureaplasma species DNA had a lower microbial load at the time of follow-up amniocentesis compared with the initial amniocentesis (median [interquartile range]: 1.5×105 copies DNA/mL [1.3×105-1.7×105] vs 8.0×107 copies DNA/mL [6.7×106-1.6×108]; P=.02). CONCLUSION: Antibiotic therapy was associated with reduced intraamniotic inflammation in patients with idiopathic bleeding in the second trimester complicated by intraamniotic inflammation. Moreover, antibiotic treatment has been associated with a reduction in the microbial load of Ureaplasma species DNA in the amniotic fluid.
Keywords: druhý trimestr těhotenství; amniotic fluid; rapid point-of-care test; bacteria; Inflammation; Anti-Bacterial Agents; pregnancy; preterm birth; funisitis; Fetal Membranes, Premature Rupture; interleukin-6; abortion; Retrospective Studies; těhotenství; DNA; ceftriaxone; prematurity; Interleukin-6; microbial invasion of the amniotic cavity; chorioamnionitis; plodová voda; zánět; Ureaplasma; amniocentesis; inflammation; Amniocentesis; neonatal outcome; amniocentéza; Amniotic Fluid; nucleic acid; 16S ribosomal RNA; biomarker; clarithromycin; genital mycoplasma; ženské pohlaví; retrospektivní studie; Humans; Pregnancy; Uterine Hemorrhage; antibakteriální látky; polymerase chain reaction; předčasný odtok plodové vody; chorioamnionitida; sterile intraamniotic inflammation; Chorioamnionitis; Female; intraamniotic infection; interleukin 6; Pregnancy Trimester, Second; lidé; děložní krvácení